Narratives of Arab Anglophone Women and the Articulation of a Major Discourse in a Minor Literature - Sarnou, Dalal (International Studies. Interdisciplinary Political and Cultural Journal, 2014)
“It is important to stress that a variety of positions with respect to feminism, nation, religion and identity are to be found in Anglophone Arab women’s writings. This being the case, it is doubtful whether, in discussing this literary production, much mileage is to be extracted from over emphasis of the notion of its being a conduit of ‘Third World subaltern women.’” (Nash 35) Building on Geoffrey Nash’s statement and reflecting on Deleuze and Guattari’s conceptualization of minor literature and Gloria Anzaldua’s Borderland(s), we will discuss in this paper how the writings of Arab Anglophone women are specific minor and borderland narratives within minor literature(s) through a tentative (re)localization of Arab women’s English literature into distinct and various categories. By referring to various bestselling English works produced by Arab British and Arab American women authors, our aim is to establish a New taxonomy that may fit the specificity of these works.